2005
DOI: 10.1016/j.chemgeo.2005.01.006
|View full text |Cite
|
Sign up to set email alerts
|

An X-ray absorption spectroscopy study of argutite solubility and aqueous Ge(IV) speciation in hydrothermal fluids to 500 °C and 400 bar

Abstract: Dissolution of synthetic argutite (GeO 2 , tetragonal, rutile-like) in pure water, and local atomic structure around Ge(IV) in aqueous solution were characterized by in situ X-ray Absorption Fine Structure (XAFS) spectroscopy at the Ge K-edge using a new high temperature-high pressure cell. XAFS transmission and fluorescence spectra were collected from germanic acid aqueous solutions of 0.02 to 0.09 mol Ge/kg H 2 O at ambient pressure and temperature, and from a 0.04 mol Ge/kg H 2 O solution at 400 bar from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 67 publications
(94 reference statements)
4
68
0
Order By: Relevance
“…measured in the transmission mode [24]. This height is proportional to the density of the sample, the amount of dissolved absorbing species and the path length (l) of the X-ray beam inside the sample (constant, see right inset on Fig.…”
Section: Concentration Of the Species In Solutionmentioning
confidence: 99%
“…measured in the transmission mode [24]. This height is proportional to the density of the sample, the amount of dissolved absorbing species and the path length (l) of the X-ray beam inside the sample (constant, see right inset on Fig.…”
Section: Concentration Of the Species In Solutionmentioning
confidence: 99%
“…A weighed amount of silver chloride, which is weakly soluble at ambient 170 temperature (< 0.001m), was pressed in pellets and loaded in the experimental cell. Total dissolved silver 171 concentration in solution was measured from the absorption edge height in transmission mode (Pokrovski et al, sample space probed by X-rays, were still observed for some experiments above 300°C (Table 1), it did not affect Silver in hydrothermal fluids 8 described in detail elsewhere (Pokrovski et al, 2005b(Pokrovski et al, , 2006 …”
Section: Introduction 67 68mentioning
confidence: 99%
“…The available GeO 2 solubility experiments and X-ray absorption spectroscopy studies of Ge-bearing aqueous solutions [4,7,8] unambiguously demonstrate that the uncharged tetra-hydroxide Ge(OH) 4 is by far the dominant species in aqueous solution from acidic to alkaline pH (1 < pH < 9) over a wide temperature, T, (298-723 K) and pressure, P, (0.1-50 MPa) range. The thermodynamic properties of Ge(OH) 4 (aq) derived from GeO 2 (s) solubility measurements using the HKF equation of state [8] are, however, valid only for dense aqueous fluids (pure water density >0.5 g cm À3 ) due to intrinsic limitations of the HKF model [10][11][12]. Other alternative models describing mineral solubilities such as the density model [8,13,14] applied to GeO 2 -water systems may be subjected to large errors beyond the T-P range covered by measurements because of an entirely empirical nature of the model coefficients.…”
Section: Introductionmentioning
confidence: 92%
“…In geochemistry, germanium is an important tracer of continental weathering and riverine flux [3,4], hydrothermal activity [4,5], and organic matter impact [6,7]. This is because in some geological contexts germanium behaves differently from silicon rendering the Ge/Si ratio in waters to be sensitive to the presence of clays and iron hydroxides, organic ligands, reduced sulphur, and temperature [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation